Monoclonal Antibodies: A Therapeutic Option for the Treatment of Ophthalmic Diseases of the Eye Posterior Segment - Catalina Ayón; Daniel Castán; Adrián Mora; Dunia Naranjo; Francini Obando; Juan José Mora (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The eye is an organ that allows us to observe the outside world. Pathologies of the eye's posterior segment, such as glaucoma, macular degeneration, diabetic retinopathy, uveitis, and retinoblastoma, cause vision loss. Traditional treatments consist of applying topical medications that do not penetrate properly or using high doses that generate adverse effects. Different laser surgeries stop the pathology's progression but do not allow visual improvement. So, an alternative is to use monoclonal antibodies, proteins produced by different processes that selectively bind to metabolites associated with diseases, reducing the adverse effects of traditional treatments and improving the application of the drug in the area. The two main molecular targets are TNF (adalimumab, infliximab, and certolizumab pegol) and VEGF (bevacizumab and ranibizumab); other possibilities are under investigation.